Effect of Constraints of Defense on Locomotors Pointing Behaviors in Elite Handball Player - Mohammadali Esmaeilzadeh; Mehdi Shahbazi; Ali Akbar Jaberimoghaddam; Shahzad Tahmasebi; Elham Shirzad (University of Tehran, 2022)
Behavioral studies in team sports are typically constrained by dynamic factors, such as positioning of defenders for interception. Handball player have to coordinate their steps when running to throw a ball on goal from a different positions. In this study were analyzed the movement patterns during locomotors pointing, throwing velocity and accuracy of 12 succesful elite handball players under defensive constraints (defender- absent, defender-far, defender-near, or defender pairing). It was captured data from the locomotors patterns of the attacking participant by speed camera with 120Hz, throwing speed by sports radar gun and throwing accuracy by camera. ANOVA with repeated measures and Bonferroni post hoc test and Friedman test was used to analyze effects of these constraints on gait and throwing parameters. In addition to Pearson and Spearman correlation coefficient test was used to analyze speed-accuracy trade off (P<0.05). The results revealed significant differences in overall mean movement velocity, first and second step mean velocity, first and second step mean length. For the mean foot/gate area distance variability was shown pattern of ascending/descending variability in all defense conditions. Since regulation of offensive players was continuous and based on perception of current and required behaviors, results supported from perception-action coupling and prospective control models of locomotors pointing. Also it is suggested that the technical aspects of the running and throwing in handball can affect by nested tasks constraints.